Resource use and costs in patients with poorly controlled type 2 diabetes mellitus and obesity in routine clinical practice in Spain. (1st September 2020) - Díaz-Cerezo, Silvia; Romera, Irene; Sicras-Mainar, Antoni; López-Simarro, Flora; Dilla, Tatiana; Artime, Esther; Reviriego, Jesús
Abstract: Objective: To compare healthcare resource use (HRU) and annual costs in type 2 diabetes mellitus (T2DM) patients with poor glycaemic control and obesity versus good glycaemic control without obesity. Methods: Observational retrospective study based on the analysis of electronic medical records from the BIG-PAC database, with one year of follow-up. T2DM patients aged ≥30 years who requested medical care during 2013 were included. Annual HRU and costs per patient were compared between a reference group (HbA1c ≥ 8%, BMI ≥30 kg/m 2, receiving ≥2 oral antidiabetic drugs [OADs]) and a control group (HbA1c < 7% and BMI <30 kg/m 2 ). Direct and indirect costs (lost productivity) were analysed. Cost comparisons across groups were made using the analysis of covariance (ANCOVA) for each cost component, with age, sex, time from diagnosis, Charlson comorbidity index, OAD number and sex by group interaction as covariates. Results: During the follow-up, patients in the reference group ( N = 2709) had a greater HRU than those in the control group ( N = 5266), especially in the number of primary care (PC) visits (11.8 vs. 9.8; 95%CI: 11.5–12.1 vs. 9.6–10.0) and days of hospitalization (1.1 vs 0.6; 95%CI: 1.0–1.2 vs. 0.5–0.7). The main components of the total cost were hospital admissions (24.5%), productivity losses (16.3%), complementary tests (14.4%), PC visits (14.2%) and medication (13.6%) in the reference group and medication (19.6%), hospital admissions (18.7%) and PC visits (18.2%) in the control group. The corrected mean annual cost per patient was higher in the reference than in the control group: €1804 vs. €1309; p < .001. Conclusions: Poor glycaemic control and obesity in T2DM patients were associated with increased HRU and costs in routine clinical practice.